Binary signals design to control the matrix converter in the context of smart grids - Gorp, Jeremy Van; Caussy, Mohunparsad; Gillot, Cyrille (IFAC-PapersOnLine, 2017)
The power converters are becoming increasingly used in modern grid so as to optimize the energetic exchanges. However their effective control remains a vast subject of study. This paper focus on the hybrid control of a matrix converter integrated in a smart grid. A binary control law is designed in order to ensure the stabilization of input and output phases of the converter. Based on a bilinear modeling and a state transformation, a cascade control is proposed. A sliding mode controller computes a new reference signal for the converter in function of the input variables. An approach based on a convex optimization procedure is designed in order to ensure the stabilization of the converter. Simulation results highlight the effectiveness of the proposed method.